A Review on Iontophoresis: A Noble Drug Delivery Tool for Management of Plantar Fasciopathy Using Ayurveda Drugs - Vivek Singh Bhadauria; Narinder Singh; Hemantha Kumar; Monika Singh; Satya Santosh Sahoo (AYUSHDHARA, 2024)
Iontophoresis is an innovative transdermal drug delivery technique that uses electrical currents to enhance the permeation of drugs through the skin. This method holds significant promise for Ayurveda, a traditional Indian system of medicine that emphasizes holistic healing. This review discusses the mechanisms, applications, advantages, and challenges of using iontophoresis and development of Iontophoresis protocol for Ayurveda drugs. This review article explores the potential of iontophoresis as a transdermal drug delivery method specifically tailored for Ayurvedic medications. Iontophoresis employs electrical currents to facilitate drug absorption through the skin, thus addressing traditional challenges such as low bioavailability and targeted delivery of Ayurvedic formulations. The authors discuss the underlying mechanisms of iontophoresis, including electromigration and electroporation, which enhance drug permeability and absorption. It proposes that this technique aligns well with Ayurvedic principles by allowing for the localized treatment of conditions such as pain and inflammation, thus enhancing therapeutic outcomes. However, the article also addresses significant challenges, such as skin irritation, compatibility of herbal ingredients with iontophoresis, the need for specialized equipment, and regulatory hurdles. It underscores the importance of further research to validate the effectiveness of iontophoresis in Ayurveda and to refine treatment protocols. In conclusion, iontophoresis offers a promising intersection between traditional Ayurvedic practices and modern technology, potentially transforming the delivery of Ayurvedic treatments. Future studies are essential for optimizing formulations and overcoming existing barriers to implementation in clinical settings.